Theory and practice in forage germ-plasm collection - Lazier, John R. (International Development Research Centre, 1985)
Discusses the theoritical and practical aspects of forage germ-plasm collection. Describes the value of the germ plasm pool, characteristics of forage plants, identification of collection areas, sampling strategy, numbers of plants sampled per size, amount of seed per accession, number of accession in a collection and rate of collection. Gives also a brief description of the collection trip including necessary trip equipment, daily routine, ILCA accession sheets.